Shaping Gen Z Careers: The Influence of Supervisor and Co-Worker Relationships, and Person-Organization Fit on Conversion Intentions in Tangerang - Kojongian, Alvin Karmel; Setiorini, Amanda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the crucial role of internship programs for college students in alignment with the 2045 Golden Indonesia Vision to enhance human resource competitiveness. Focusing on Generation Z in Tangerang Regency, we investigate how intern-supervisor relationships, intern-coworker interactions, and person-organization fit influence conversion intentions to permanent positions. Using a quantitative approach, we surveyed 270 respondents, revealing significant positive correlations between these factors and conversion intentions through multiple regression analysis (SPSS26). Our findings highlight the need for companies to cultivate strong relationships within internship programs, as this can encourage interns to transition into permanent roles. This research offers valuable insights into enhancing workplace dynamics and supporting Generation Z’s career aspirations.